Treatment delay and the risk of relapse in pediatric acute lymphoblastic leukemia. (2nd January 2017) - Yeoh, Amelia; Collins, Anna; Fox, Kahlia; Shields, Sarah; Ritchie, Petra; Kirby, Maria; Revesz, Tamas
ABSTRACT: Delays or interruptions in chemotherapy due to toxicity such as neutropenia or severe infections are common in the treatment of pediatric acute lymphoblastic leukemia (ALL). Based on the reports of worse outcomes in children with poorer compliance with therapy, there has been concern that toxicity-induced therapy interruptions could also compromise treatment outcome. In a retrospective study of treatment delays in our hospital between 2003 and 2013, the case notes of 141 patients were reviewed. The cumulative lengths of delays during the whole length of chemotherapy, during the intensive phase of treatment, and during maintenance treatment were analyzed. Within these categories, delays were split between less and more than the median value. The risk of relapse did not differ between patients with a longer or shorter delay during the total length of treatment or during the intensive phase. In addition, there was a trend when comparing patients above vs below the mean in length of treatment delays during maintenance, and there was a statistically significant difference in relapses when comparing patients in the lowest and highest quartiles of maintenance delays, with fewer relapses among those patients in the highest quartile for treatment delays.